Forage seeding in rangelands increases production and prevents weed invasion - Josh Davy; Katherine Dykier; Tony Turri; Elise Gornish (California Agriculture, 2017)
Increasing forage productivity in the Sierra foothill rangelands would help sustain the livestock industry as land availability shrinks and lease rates rise, but hardly any studies have been done on forage selections. From 2009 to 2014, in one of the first long-term and replicated studies of seeding Northern California's Mediterranean annual rangeland, we compared the cover of 22 diverse forages to determine their establishment and survivability over time. Among the annual herbs, forage brassica (Brassica napus L.) and chicory (Cichorium intybus L.) proved viable options. Among the annual grasses, soft brome (Bromus hordeaceus) and annual ryegrass (Lolium multiflorum) performed well. However, these species will likely require frequent reseeding to maintain dominance. Long-term goals of sustained dominant cover (> 3 years) are best achieved with perennial grasses. Perennial grasses that persisted with greater than 50% cover were Berber orchardgrass (Dactylis glomerata), Flecha tall fescue (Lolium arundinaceum) and several varieties of hardinggrass (Phalaris aquatica L., Perla koleagrass, Holdfast, Advanced AT). In 2014, these successful perennials produced over three times more dry matter (pounds per acre) than the unseeded control and also suppressed annual grasses and yellow starthistle (Centaurea solstitialis L.) cover.